Microstructure, optical and electrical properties of sputtered HfTiO high-k gate dielectric thin films. Issue 10 (1st August 2016) - Jiang, S.S.; He, G.; Gao, J.; Xiao, D.Q.; Jin, P.; Li, W.D.; Lv, J.G.; Liu, M.; Liu, Y.M.; Sun, Z.Q.
Abstract: The microstructure, optical and electrical properties of HfTiO high-k gate dielectric thin films deposited on Si substrate and quartz substrate by RF magnetron sputtering have been investigated. Based on analysis from x-ray diffraction (XRD) measurements, it has been found that the as-deposited HfTiO films remain amorphous regardless of the working gas pressure. Meanwhile, combined with characterization of ultraviolet-visible spectroscopy (UV–vis) and spectroscopy ellipsometry (SE), the deposition rate, band gap and optical properties of sputtered HfTiO gate dielectrics were determined. Besides, by means of the characteristic curves of high frequency capacitance–voltage ( C – V ) and leakage current density–voltage ( J – V ), the electrical parameters, such as permittivity, total positive charge density, border trap charge density, and leakage current density, have been obtained. The leakage current mechanisms are also discussed. The energy band gap of 3.70 eV, leakage current density of 1.39×10 −5  A/cm 2 at bias voltage of 2 V, and total positive charge density and border trap charge density of 9.16×10 11  cm −2 and 1.3×10 11  cm −2, respectively render HfTiO thin films deposited at 0.6 Pa, potential high-k gate dielectrics in future CMOS devices.